2020
DOI: 10.1101/2020.05.28.20115725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glaucoma home-monitoring using a tablet-based visual field test (Eyecatcher): An assessment of accuracy and adherence over six months

Abstract: Purpose: To assess accuracy and adherence of visual field (VF) home-monitoring in a pilot sample of glaucoma patients. Design: Prospective longitudinal observation. Methods: Twenty adults (median 71 years) with an established diagnosis of glaucoma were issued a tablet-perimeter (Eyecatcher), and were asked to perform one VF home-assessment per eye, per month, for 6 months (12 tests total). Before and after home-monitoring, two VF assessments were performed in-clinic using Standard Automated Perimetry (SAP; 4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…7 Trials of computer based vision measurements have involved giving participants laptops with known screen parameters. 8,9 Smartphones can be used to measure visual acuity, 10 but a 2015 review of smartphone vision testing apps found poor agreement with conventional vision tests, particularly for people with severe vision impairment. 11 Further, more than 1 in 8 people in the UK do not use the internet, including 48% of those over 75 years of age, 12 all of whom are classified as being of at least moderate risk of complications from Covid-19.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…7 Trials of computer based vision measurements have involved giving participants laptops with known screen parameters. 8,9 Smartphones can be used to measure visual acuity, 10 but a 2015 review of smartphone vision testing apps found poor agreement with conventional vision tests, particularly for people with severe vision impairment. 11 Further, more than 1 in 8 people in the UK do not use the internet, including 48% of those over 75 years of age, 12 all of whom are classified as being of at least moderate risk of complications from Covid-19.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…52 The tests also have the potential to be used as a tool for home monitoring; this should be the subject of future studies. While there is a relatively large and growing body of literature on the use of technology for home monitoring of ophthalmological conditions such as glaucoma 53,54 and AMD, 55,56 home monitoring in DR/DME has very little mention in the existing research literature. This seems strange given DR/DME patients are likely ideal candidates for a home-monitoring programme as many will already be accustomed to self-monitoring other aspects of their condition.…”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%